Regularizar a terra: um desafio para as populações tradicionais de Gurupá - TRECCANI, Girolamo Domenico (Universidade Federal do Pará, 2013)
The traditional populations of the Amazon, from the early eighties of the XXth century, rediscovered the possibility of affirmation of their identity and rights and they have started to fight towards these endeavors. A basic moment of this process was to recognize their socioeconomic and cultural heterogeneity as indigenous remnant people of the communities like Maroons, people living from the land, peasant farmers and small communities living along the Amazon’s rivers. In the search of the recognition of their rights over the lands that they occupy and to the natural resources that exist in the land itself, they realized that the legislation did not present norms that reflect satisfactorily their experiences of life. Innovative legal instruments are appearing on this regard and they follow the units of conservation of direct use and other modalities of agrarian regulations of agroecological nature. In this perspective, the experience of the people living of the land of the city of Gurupa, state of Para, was researched and it is argued on the basis of qualitative and quantitative evidences produced under an inter-disciplinary orientation, as far as methodology of investigation is concerned. It has also been considered the history and the latest environmental and socio-economic trends referring to the place/region under consideration. This approach implied the use of a set of images of iconographic importance and in the discussion of concepts of traditional populations, sustainable development and public politics. Throughout the thesis, the academic literature, the specialized documentation and the data produced in locus disclose the legal-agrarian problematic among the people living of the land of Gurupa as the central element and, at the same time, it brings together the transformations that are about to affect them. Along these lines, there is a process of occupation of lands permeated by conflicts of interest, abuses and even violence; the present laws which come from the past are full of contradictions. In addition, there is also the existence of documents from registry offices dominated by legal inconsistencies. Facing this situation, these workers and specialists sensible to their cause appear as successful in many issues when demanding from the public authority possibilities that could guarantee legal security to them in view of their remaining lands.